Developing A Learning Media on Limit of Algebraic Functions by Using Google Forms - Neni Rifatul Afiah; Heni Pujiastuti (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The objective of the research is to develop a valid and practical learning media using google forms for material on the limit of algebraic functions. The type of research is Research and Development (R & D) using the ADDIE model in the process of developing a learning media. The ADDIE model development procedure is Analysis, Design, Development, Implementation, and Evaluation in validation results of development research involved six students at SMAN 11 Pandeglang and six teachers who are media experts and material experts. The results of this study are (1) Produce mathematics learning media using google forms with good qualifications on the material limit of algebraic functions, (2) Media expert assessments of well-qualified learning media products, and (3) Average results of validation by students on media products with good qualifications. Keywords: learning media, e-learning, google forms, limits of algebraic functions.